Endoscopic Management of Post-Polypectomy Bleeding - Aditya Gutta; Mark A. Gromski (Korean Society of Gastrointestinal Endoscopy, 2020)
Post-polypectomy bleeding (PPB) is one of the most common complications of endoscopic polypectomy. There are multiple risk factors related to patient and polyp characteristics that should be considered. In most cases, immediate PPB can be effectively managed endoscopically when recognized and managed promptly. Delayed PPB can manifest in a myriad of ways. In severe delayed PPB, resuscitation for hemodynamic stabilization should be prioritized, followed by endoscopic evaluation and therapy once the patient is stabilized. Future areas of research in PPB include the risks of direct oral anticoagulants and of specific electrosurgical settings for hot-snare polypectomy vs. cold-snare polypectomy, benefits of closure of post-polypectomy mucosal defects using through-the-scope clips, and prospective comparative evaluation of newer hemostasis agents such as hemostatic spray powder and over-the-scope clips.